Otimização da produção diária de empreendimentos de geração distribuída considerando aspectos técnicos e ambientais - Carvalho, Fernando Aparecido (2015)
By its modular feature a Distributed Generation project can be up to several generating units, which represents an alternative to better match supply and demand. This paper presents a multi-objective modeling to optimize the number of generating units from distributed generators considering minimizing electrical losses on the network and also CO2 emissions of distributed generators, considering renewable primary and non-renewable sources, as well as penetration of restrictions and maximum quantities generation units. The optimization model solution process employs genetic algorithms and weighting of the objectives of the method for obtaining a set of Pareto optimal solutions. Case studies with representative grids are presented for testing, analysis and validation of the proposed methodology.